Effect of acid etching time on demineralization of primary and permanent coronal dentin - Scheffel, Débora Lopes Salles [UNESP]; Tenuta, Lívia Maria Andaló; Cury, Jaime Aparecido; Hebling, Josimeri [UNESP] (My University, 2012)
Purpose: To determine the effect of acid etching time on dentin calcium solubilization and to compare the solubilization rate of primary and permanent dentin when etched for the same period of time. Methods: Flat coronal dentin surfaces were produced on primary (n=8) and permanent (n=8) sound teeth. Three 2 mm-diameter areas were delimited on each surface and assigned to 5, 10 or 15 seconds of acid etching. Five microliters of 35% H3PO4 were applied on each area during the preset times, and 4 uL were retrieved for analysis. The amount of calcium was determined colorimetrically using Arsenazo III reagent and expressed as ug Ca/mm2 of dentin. Data were subjected to two-way ANOVA, Tukey's test and linear regression (α=5%). Results: For both primary and permanent dentin, a statistically significant correlation was observed between acid etching time and calcium concentration (primary dentin R2= 0.79; permanent dentin R2= 0.73). Mean (sd) values of dissolved primary dentin after 5, 10 and 15 seconds were 1.00 (0.25), 1.74 (0.11) and 2.30 (0.42), whereas for permanent dentin the values were 0.47 (0.13), 0.89 (0.36) and 1.38 (0.20) ug Ca/mm2, respectively. Greater calcium solubilization (P< 0.05) was detected for primary dentin than for permanent dentin after all acid etching times. © 2012 P & G.